2019
DOI: 10.3390/jcs3020061
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of TiO2- and ZnO-Decorated with Silver Nanoparticles

Abstract: This work emphasizes the use of the silver decorative method to enhance the antibacterial activity of TiO2 and ZnO nanoparticles. These silver-decorated nanoparticles (hybrid nanoparticles) were synthesized using sodium borohydride as a reducing agent, with the weight ratio of Ag precursors/oxide nanoparticles = 1:30. The morphology and optical properties of these hybrid nanoparticles were investigated using transmission electron microscopy (TEM), X-ray diffraction (XRD) patterns, and UV-Vis spectroscopy. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(44 citation statements)
references
References 80 publications
4
40
0
Order By: Relevance
“…Moreover, the deposition of Au particles on the surface of ZnO NPs, even at a low molar ratio of ZnO/Au (0.2%), significantly improves the photocatalytic antibacterial activity of ZnO [ 147 ]. Furthermore, Ag-TiO 2 nanocomposite demonstrates antibacterial activity against S. aureus biofilms [ 93 , 148 , 149 ]. It was shown that the inclusion of a 2% composite significantly reduced the formation of biofilms on the surface of the composite resin [ 150 ].…”
Section: Metal Oxide Nanocomposites Against Plankton Cells and Biomentioning
confidence: 99%
“…Moreover, the deposition of Au particles on the surface of ZnO NPs, even at a low molar ratio of ZnO/Au (0.2%), significantly improves the photocatalytic antibacterial activity of ZnO [ 147 ]. Furthermore, Ag-TiO 2 nanocomposite demonstrates antibacterial activity against S. aureus biofilms [ 93 , 148 , 149 ]. It was shown that the inclusion of a 2% composite significantly reduced the formation of biofilms on the surface of the composite resin [ 150 ].…”
Section: Metal Oxide Nanocomposites Against Plankton Cells and Biomentioning
confidence: 99%
“…[40]. Furthermore, TiO 2 and ZnO nanoparticles have shown to promote the antibacterial activity of 8 mm against bacteria (S. aureus-ATCC 25923) and (E. coli-ATCC 25922) [41]. and antimicrobial activities among other crystalline structures.…”
Section: Resultsmentioning
confidence: 99%
“…e use of TiO 2 in photovoltaics is also promising and practically significant [15,16]. ese are only a few examples of titanium (IV) oxide applications, based on prominent characteristics of TiO 2 such as structural, adsorption, (photo) catalytic, and electrical properties, which, depending on the synthesis conditions, can differ significantly [17][18][19].…”
Section: Introductionmentioning
confidence: 99%